2003
DOI: 10.1210/jc.2003-030131
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule 1 Gene Polymorphisms in Graves’ Disease

Abstract: It was recently suggested that genetic factors could play a major role in the development of Graves' disease (GD). The aim of the present study was to evaluate the frequency of the c.721G-->A polymorphism and the c.1405A-->G polymorphism of the intercellular adhesion molecule 1 (ICAM-1) gene in subjects with GD compared with that in healthy controls, because ICAM-1 was found to play a key role in lymphocyte infiltration into the thyroid gland and the concentration of the soluble form of ICAM-1 correlates signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
2
28
3
Order By: Relevance
“…The associations between age at onset and different human leukocyte antigen genotypes [28,29] and ICAM-1 gene alleles [30] have been reported. The criteria we used to stratify the patients into those with early and later ages of onset of disease were based on the epidemiological observations of the highest risk of the onset of GD [2].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between age at onset and different human leukocyte antigen genotypes [28,29] and ICAM-1 gene alleles [30] have been reported. The criteria we used to stratify the patients into those with early and later ages of onset of disease were based on the epidemiological observations of the highest risk of the onset of GD [2].…”
Section: Discussionmentioning
confidence: 99%
“…ICAM1 is constitutively expressed in cells involved in immune response and induced on other cells, including endothelial and epithelial cells. It has a wellknown role in inflammation-related processes and immune surveillance, and derangements of its expression have been implicated in the development of a variety of inflammatory diseases (23)(24)(25) as well as in tumor progression of several cancers, including breast cancer (26 -28). ICAM1 is also involved in transmembrane signal transduction after binding to ␤2 integrin ligands and multimer formation (29), activating the mitogen-activated protein kinase pathway (30) and eventually transcription factors like AP-1 that regulate cell proliferation events (31).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study serum L-selectin and Intercellular Adhesion Molecule-1 (ICAM-1) were found to be elevated in patients with active GO, suggesting enhanced T cell recruitment [10]. Moreover the ICAM-1 gene polymorphism could influence the intensity and duration of the autoimmunity process and the infiltration of orbital tissues [11].…”
Section: Introductionmentioning
confidence: 97%